2017
DOI: 10.1073/pnas.1713563114
|View full text |Cite
|
Sign up to set email alerts
|

HIF and HOIL-1L–mediated PKCζ degradation stabilizes plasma membrane Na,K-ATPase to protect against hypoxia-induced lung injury

Abstract: Organisms have evolved adaptive mechanisms in response to stress for cellular survival. During acute hypoxic stress, cells down-regulate energy-consuming enzymes such as Na,K-ATPase. Within minutes of alveolar epithelial cell (AEC) exposure to hypoxia, protein kinase C zeta (PKCζ) phosphorylates the α-Na,K-ATPase subunit and triggers it for endocytosis, independently of the hypoxia-inducible factor (HIF). However, the Na,K-ATPase activity is essential for cell homeostasis. HIF induces the heme-oxidized IRP2 ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…It has been reported that IFN-α and IFN-γ can regulate the expression of LUBAC components in SHARPIN-deficient mice (43). In our mod-HOIL-1L has several LUBAC-independent functions, such as acting as an E3 ubiquitin ligase to target proteins such as PKCζ for degradation as seen in adaptation to hypoxia and cancer (23,31,39). Nondenaturing native gel electrophoresis of lysates from WT AT2 cells or A549 cells exposed to WSN in vitro revealed that HOIL-1L runs consistent with the 600 kDa molecular weight of LUBAC (25) ( Figure 4C and Supplemental Figure 5K).…”
Section: Iav Infection Increases Hoil-1l Inmentioning
confidence: 65%
See 2 more Smart Citations
“…It has been reported that IFN-α and IFN-γ can regulate the expression of LUBAC components in SHARPIN-deficient mice (43). In our mod-HOIL-1L has several LUBAC-independent functions, such as acting as an E3 ubiquitin ligase to target proteins such as PKCζ for degradation as seen in adaptation to hypoxia and cancer (23,31,39). Nondenaturing native gel electrophoresis of lysates from WT AT2 cells or A549 cells exposed to WSN in vitro revealed that HOIL-1L runs consistent with the 600 kDa molecular weight of LUBAC (25) ( Figure 4C and Supplemental Figure 5K).…”
Section: Iav Infection Increases Hoil-1l Inmentioning
confidence: 65%
“…by flow cytometry using defined lineage-specific cell surface markers and gated as described in Methods and but instead express a 30-kDa truncated variant (21) that results in reduced levels of 600-kDa LUBAC (32) as well as impaired NF-κB signaling (21). Immunoblots of mouse alveolar type 2 (AT2) cell lysates using a specific antibody against either the C-terminus (21,31) or the N-terminus of HOIL-1L (33) showed a band at approximately 55 kDa in WT AT2 cells, corresponding to the molecular weight of full-length HOIL-1L, that was absent in SPC Cre /HOIL-1L fl/fl AT2 cell lysates (Supplemental Figure 2, A and B). Additionally, using the HOIL-1L N-terminus antibody, we observed a low-abundance band at approximately 30 kDa in SPC Cre /HOIL-1L fl/fl AT2 cells (Supplemental Figure 2A and ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia results in oxidative stress and is known to damage the NKA complex through at least two mechanisms. The oxidized NKA complex is proteosomally degraded resulting in decrease in the expression of this ion pump on the cell membrane [14][15][16][17]. As a result, there is membrane depolarization and hence, cell death.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is membrane depolarization and hence, cell death. Oxidative stress also is known to activate protein kinase C (PKC) which in turn phosphorylates NKA [14][15][16][17][18][19]. The phosphorylated form of NKA is internalized from the cell membrane, again resulting in membrane depolarization and cell death (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%